Systemic and tumor-specific inflammatory markers VCAM-1 and ICAM-1 as indicators of extent of surgery and oncologic outcome in advanced ovarian cancer - Okan Gultekin; Jordi Gonzalez-Molina; Dhifaf Sarhan; Nina Groes-Kofoed; Mahmood Ul Hassan; Kaisa Lehti; Sahar Salehi (Translational Oncology)
Background: Cytoreductive surgery in advanced ovarian cancer presents significant challenges and there is a need for an improved patient selection to surgical treatment. Cytokines and adhesion molecules are key regulators of immune responses, playing crucial roles in tumor cell adhesion, metastasis, and immune evasion. They shape the tumor microenvironment and influence systemic immunity, ultimately affecting cancer progression. Despite their recognized significance in cancer biology, the potential of cytokines as predictive biomarkers for surgical complexity and recurrence in ovarian cancer remains insufficiently characterized. This study aimed to elucidate the correlation between inflammatory cytokines and surgical outcomes, to identify reliable liquid or tissue-based biomarkers that could enhance patient stratification and support preoperative decision-making in ovarian cancer management. Methods: The Concentration of 10 inflammatory cytokines and 2 adhesion molecules concentrations were measured by Luminex based assay in blood, tumor tissue, and ascitic fluid samples from patients with advanced ovarian cancer prior to cytoreductive surgery. Clinical data were prospectively collected. Correlations between cytokines and adhesion molecules levels and surgical complexity, as well as disease/cancer recurrence, were assessed using Pearson two-tail statistical test analyses. The association between adhesion molecules and surgical extent, and recurrence was analysed using logistic regression yielding odds ratios (OR) with 95 % confidence intervals, adjusted for relevant covariates. The diagnostic accuracy of biomarker candidates was evaluated using receiver operating characteristic (ROC) curve analysis Results: In blood, higher VCAM-1 and ICAM-1 levels correlated with lower surgical complexity scores, while ascitic VCAM-1 was linked to longer surgical durations. CXCL-12 in tumor and IL-32 in ascites were positively correlated with increased surgery duration, indicating their role in systemic inflammation. Elevated VCAM-1 and ICAM-1 levels in tumor tissue were strongly associated with increased cancer recurrence risk, suggesting their involvement in metastasis and immune evasion. Traditional preoperative markers, including albumin and CRP, did not correlate significantly with surgical complexity, highlighting the need for novel biomarkers. In the adjusted multivariable regression model, VCAM-1 in blood was associated with recurrence, OR 10.1 (95 % CI, 1.30-77.8; p=0.027). Similarly, VCAM-1 in blood demonstrated exceptional predictive capability, Area Under Curve=0.886 with cutoff point of 0.696. Conclusions: Inflammatory markers can serve as valuable predictors of surgical complexity and recurrence in advanced ovarian cancer. Particularly the levels of VCAM-1 in blood was identified as a potential predictive marker to be tested in adequately powered clinical studies. Incorporating these markers into preoperative assessments could improve surgical planning and enhance patient stratification. Further validation and mechanistic studies are needed to fully understand their role in ovarian cancer progression. Trial registration: ClinicalTrials.gov nr: NCT04065009, European Union Clinical Trials Register nr: 2019-003299-38/SE